Human eIF3b and eIF3a serve as the nucleation core for the assembly of eIF3 into two interconnected modules: the yeast-like core and the octamer - Wagner, Susan; Herrmannová, Anna; Šikrová, Darina; Valášek, Leoš Shivaya (Nucleic acids research, 2016)
The 12-subunit mammalian eIF3 is the largest and most complex translation initiation factor and has been implicated in numerous steps of translation initiation, termination and ribosomal recycling. Imbalanced eIF3 expression levels are observed in various types of cancer and developmental disorders, but the consequences of altered eIF3 subunit expression on its overall structure and composition, and on translation in general, remain unclear. We present the first complete in vivo study monitoring the effects of RNAi knockdown of each subunit of human eIF3 on its function, subunit balance and integrity. We show that the eIF3b and octameric eIF3a subunits serve as the nucleation core around which other subunits assemble in an ordered way into two interconnected modules: the yeast-like core and the octamer, respectively. In the absence of eIF3b neither module forms in vivo, whereas eIF3d knock-down results in severe proliferation defects with no impact on eIF3 integrity. Disrupting the octamer produces an array of subcomplexes with potential roles in translational regulation. This study, outlining the mechanism of eIF3 assembly and illustrating how imbalanced expression of eIF3 subunits impacts the factor's overall expression profile, thus provides a comprehensive guide to the human eIF3 complex and to the relationship between eIF3 misregulation and cancer.
Keywords: Saccharomyces cerevisiae; Eukaryotic Initiation Factor-3; HeLa buňky; down regulace; multiproteinové komplexy; proliferace buněk; Protein Multimerization; multimerizace proteinu; eukaryotický iniciační faktor 3; lidé; Down-Regulation; HeLa Cells; Cell Proliferation; Humans; Multiprotein Complexes